Data Analysis, Machine Learning and Applications c - Preisach, Christine; Burkhardt, Hans.; Schmidt-Thieme, Lars.; Decker, Reinhold; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
Data analysis and machine learning are research areas at the intersection of computer science, artificial intelligence, mathematics and statistics. They cover general methods and techniques that can be applied to a vast set of applications such as web and text mining, marketing, medical science, bioinformatics and business intelligence. This volume contains the revised versions of selected papers in the field of data analysis, machine learning and applications presented during the 31st Annual Conference of the German Classification Society (Gesellschaft für Klassifikation - GfKl). The conference was held at the Albert-Ludwigs-University in Freiburg, Germany, in March 2007.
Classification -- Clustering -- Multidimensional Data Analysis -- Analysis of Complex Data -- Exploratory Data Analysis and Tools for Data Analysis -- Marketing and Management Science -- Banking and Finance -- Business Intelligence -- Text Mining, Web Mining, and the Semantic Web -- Linguistics -- Data Analysis in Humanities.
Keywords: Computer science; Information technology; Business -- Data processing; Data mining; Artificial intelligence; Statistics; Computer Science; Artificial Intelligence (incl. Robotics).; Statistics, general; IT in Business; Data Mining and Knowledge Discovery; Electronic books